A rare case report on ovotesticular disorders of sex development (DSD) 46XY variant - Swain, Sujata; Pradhan, Lopamudra; Satpathy, R. N.; Mahapatra, P. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovotestis refers to the histology of a gonad that contains both ovarian follicles and testicular tubular elements. Ovotesticular DSD is a rare condition characterized by mixed ovarian and testicular tissue. Majority have a 46,XX karyotype, 7% have 46,XY karyotype and 10-40% exhibit chromosomal mosaicism. Here, we report the case of a boy with a 46,XY karyotype diagnosed as ovotesticular DSD by gonadal biopsy. A 14 year-old reared as boy presented with came with ambiguous genitalia with no palpable gonads since birth and developed progressive virilization and gynaecomastia at puberty having curved phallus with glans, redundant prepucial skin, labia majora and hypoplastic labia minora, rudimentary vagina with small introitus was present. External urethral meatus present lower down the vestibular area above the introitus. Testicles not felt. USG - revealed definite uterus behind Urinary bladder with small intraabdominal testes. Karyotyping - 46XY Barr body present. Diagnostic laparoscopy showed Uterus with bilateral fallopian tubes. Bilateral gonadectomy done. Histopathologic examination report revealed bilateral gonadoblastoma in testis and ovotestis. Patient underwent transperitoneal excision of Mullerian remnants. Patient was discharged with an advice of cap testosterone undecanoate and regular follow up. We highlight the importance of histological and cytogenetic investigation in DSD.